2014
DOI: 10.1037/xan0000004
|View full text |Cite
|
Sign up to set email alerts
|

A three-component model of relational responding in the transposition paradigm.

Abstract: We present a new model of transposition behavior that involves 3 predictors: (a) the disparity in generalized associative strength from the previously reinforced and nonreinforced stimuli (g) to the stimuli in the testing pair; (b) relational disparity (r), the difference in the logarithmically scaled sensory values of the testing stimuli; and (c) familiarity (f), the inverse of the Euclidean distance from the testing pair to the nearest training pair in 2-dimensional stimulus space. We evaluated the model wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
(110 reference statements)
1
11
1
Order By: Relevance
“…In contrast, we found that pigeons required more extensive training to learn speed discrimination than size discrimination (Lazareva, Young, & Wasserman, 2014). However, our results were based on a comparison of two experiments conducted in different laboratories, complicating the interpretation of the data.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…In contrast, we found that pigeons required more extensive training to learn speed discrimination than size discrimination (Lazareva, Young, & Wasserman, 2014). However, our results were based on a comparison of two experiments conducted in different laboratories, complicating the interpretation of the data.…”
contrasting
confidence: 49%
“…Earlier, we reported that pigeons appeared to easily acquire simultaneous two-alternative size discrimination but not speed discrimination (Lazareva et al, 2014). In Experiment 1, we found no observable improvement in discrimination of rotational speed in a simultaneous two-alternative task after an extensive training.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…These colors were chosen based on dogs' dichromatism, as they demonstrate wavelength sensitivities of blue at a spectral peak of 555 nm and yellow at 429 nm (Jacobs et al, 1993;Neitz, Geist, & Jacobs, 1989). Three circle stimuli were used, which were constructed from an array of 12 circles used previously to test transpositions in pigeons (Lazareva, Miner, Wasserman, & Young, 2008;Lazareva, Wasserman, & Young, 2005;Lazareva, Young, & Wasserman, 2014) and illusion susceptibility in this same group of dogs . These specific stimuli were chosen as they represented a systematic array of figures.…”
Section: Methodsmentioning
confidence: 99%